Liquidity Commonality Among Asian Futures Markets - Nguyen, Vu Hong Thach (2015)
This study investigates the impact of common liquidity factors on liquidity variations of seven selected Asian stock index futures. On average, the common factors account for 10.35% of daily variations of Asian futures liquidity. In that, 8.89% is driven by regional common factors whereas global factors account for a much lower portion of 1.46% which suggests that Asian futures markets are more regionally integrated than globally integrated in liquidity. Among economic common factors, cross-border average volatility is as important as the cross-market average liquidity as they explain 5% and 4.95% of local liquidity variations, respectively. On contrary, return, on average, accounts for a much smaller portion of liquidity variations. The findings point to the existence of cross-border liquidity commonality among Asian index futures. Furthermore, liquidity commonality is found to strengthen during the 2008 Global financial crisis which is consistent with the notion that funding constraints during market declines intensify liquidity commonality. Also, as a common factor, volatility became prominent during the crisis period with the increased contribution to local liquidity variations. Overall, the results of this study are useful for international investors as they are advised to consider this source of risk in their required returns and cross-border diversification strategies. In addition, Asian policymakers and market regulators should take this dimension of market integration into account in order to design and maintain a well-functioning and stable financial market. This paper also establishes liquidity linkage between stock index and stock index futures in Asian markets. A vector autoregressive model for liquidity (liquidity, volatility, and return in stock and futures markets) is estimated. Innovations to stock and futures liquidity are significantly correlated which suggests that liquidity shocks are systemic in nature across Asian markets. There is a lead-lag relationship between liquidity of the two markets implying that liquidity of one market is informative in predicting liquidity of the other market. Generalized impulse response functions and variance decompositions indicate that past liquidity and volatility are the most important variables in forecasting future liquidity and further point to the existence of common factors that affect liquidity in both markets. The paper generally provides evidence of liquidity integration between stock and futures markets which also has implications for asset pricing, portfolio investments, policy design and implementation.